Assessment of Heavy Metal Levels in Tissues of Common Guitarfish (Rhinobatosrhinobatos) from Iskenderun and Antalya Bays, Northeastern Mediterranean Sea - Gokkus, K.; Turkmen, M. (Natl Inst Science Communication-Niscair, 2016)
Turkmen, Mustafa/0000-0001-6700-5947 WOS: 000389787100019 According to dry weight basis analysis, the lowest heavy metal level was generally detected in the muscle and the highest amount was determined in the intestine in both bays. Although the results of Iskenderun bay were higher than Antalya bay. When the heavy metal levels in the muscle are compared with the national and international standards, it was indicated that the metal concentrations were below the permissible limits. From this aspect, Iskenderun and Antalya bays do not contain adequate amounts of heavy metal to cause pollution. TUBITAKTurkiye Bilimsel ve Teknolojik Arastirma Kurumu (TUBITAK) [106Y210] Authors are grateful to TUBITAK for financial support (Project No:106Y210).
Keywords: Iskenderun Bay; Heavy metal; Antalya Bay; Common guitarfish; Rhinobatosrhinobatos